Answer:
-3x-y=10
Step-by-step explanation:
y+4=-3(x+2)
y+4=-3x-6
y=-3x-6-4
y=-3x-10
-3x-y=10
The value of the expression 5x – 2y + (7x – y) when x = 7 and y = -2 is 90
<h3>How to evaluate the expression?</h3>
The expression is given as:
5x – 2y + (7x – y)
Substitute x = 7 and y = –2 in the above expression
5 * 7 - 2 * -2 + (7 * 7 + 2)
Evaluate the expression
90
Hence, the value of the expression 5x – 2y + (7x – y) when x = 7 and y = -2 is 90
Read more about expressions at:
brainly.com/question/723406
#SPJ1
Answer:
It was on for 12.4 minutes
Step-by-step explanation:
Answer:
18 meters if my mental math is right.